Dexmedetomidine Mediates Neuroglobin Up-Regulation and Alleviates the Hypoxia/Reoxygenation Injury by Inhibiting Neuronal Apoptosis in Developing Rats - Gao, Yan; Zhang, Yongfang; Dong, Yunxia; Wu, Xiuying; Liu, Hongtao (Frontiers in Pharmacology, 2020)
Background: Exploring the effective therapy for neonatal hypoxic-ischemic brain injury is an important goal. This study was designed to investigate how dexmedetomidine (DEX) contribute to hypoxic brain injury. Methods: Developing Sprague-Dawley rat models of hypoxia/reoxygenation (H/R) injury were constructed to simulate neonatal hypoxic brain injury for DEX treatment. Immunohistochemistry and western blot were performed to measure neuroglobin (Ngb) protein expression in hippocampal tissues. Hippocampal neuron injury and apoptosis were detected by Nissl staining and TUNEL assay, respectively. A Morris water maze (MWM) test was performed to evaluate the long-term learning and memory function. Results: The expression of Ngb was increased following H/R model establishment and up-regulated by medium and high doses of DEX, but not up-regulated by low doses of DEX. Medium and high doses of DEX alleviated the H/R injury as well as induced the reduction of Nissl bodies and apoptosis. Besides, medium and high doses of DEX down-regulated cytosolic Cyt-c, Apaf-1, and caspase-3 in H/R injury model. MWM test showed that medium and high doses of DEX significantly shortened the escape latency and enhanced the number of platform crossings. However, low doses of DEX have no effect on Nissl bodies, mitochondrial apoptosis, expression of apoptosis-related proteins and long-term learning functions. Conclusions: DEX induced Ngb expression in H/R rat models. The neuroprotection of DEX-mediated Ngb up-regulation may be achieved by inhibiting neuronal apoptosis through the mitochondrial pathway. Findings indicated that DEX may be useful as an effective therapy for neonatal hypoxic brain injury.